MORAL TECHNIQUES. FORENSIC ANTHROPOLOGY AND ITS ARTIFACTS FOR DOING GOOD (Sociología y tecnociencia, 2013)
In many of its applications forensic anthropology is a singular discipline, midway between a bare techno-scientific exercise and a militant involvement in overcoming situations marked by human rights violations. Today, riding on an intense and transnational wave of humanitarian sensitivity, forensic anthropology has acquired a significant scientific, moral and media status, and has become a front line scientific-technical practice in the human rights field at the planetary level. This text, which analyzes some of the artifacts with which forensic anthropology represents and works on its object, aims to understand this discipline through the concept of moral technique, which, in my understanding, captures the particular tensions of this form of working for good.